2015
DOI: 10.1016/j.febslet.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

The DRBD13 RNA binding protein is involved in the insect‐stage differentiation process of Trypanosoma brucei

Abstract: Edited by Michael IbbaKeywords: DRBD13 Post transcriptional gene regulatory program Insect stage differentiation process Trypanosoma brucei a b s t r a c t DRBD13 RNA-binding protein (RBP) regulates the abundance of AU-rich element (ARE)-containing transcripts in trypanosomes. Here we show that DRBD13 regulates RBP6, the developmentally critical protein in trypanosomatids. We also show DRBD13-specific regulation of transcripts encoding cell surface coat proteins including GPEET2, variable surface glycoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…We found that cells over‐expressing the (ARE)‐regulating protein DRBD13, is also disadvantageous for cell growth. DRBD13 down‐regulates transcripts encoding cell surface coat proteins (Jha et al ., ). Although the effect of over‐expressing DRBD13 in bloodstream forms has not been evaluated, DRBD13 levels are tightly regulated in the procyclic stage, as both DRBD13 over‐expression and depletion were deleterious to the parasite's growth.…”
Section: Resultsmentioning
confidence: 97%
“…We found that cells over‐expressing the (ARE)‐regulating protein DRBD13, is also disadvantageous for cell growth. DRBD13 down‐regulates transcripts encoding cell surface coat proteins (Jha et al ., ). Although the effect of over‐expressing DRBD13 in bloodstream forms has not been evaluated, DRBD13 levels are tightly regulated in the procyclic stage, as both DRBD13 over‐expression and depletion were deleterious to the parasite's growth.…”
Section: Resultsmentioning
confidence: 97%
“…However, due to the limitations of this methodology, only one group reported success in knocking out RBPs with this approach (Alcantara et al, 2018). Accordingly, this approach is not feasible in cases where the target gene is essential, which seems to be the case for many RBPs, as reported in T. brucei through gene silencing assays (Das et al, 2012;Wurst et al, 2012;Droll et al, 2013;Fernández-Moya et al, 2014;Jha et al, 2015;Levy et al, 2015).…”
Section: Knockout Of Rbp Genesmentioning
confidence: 99%
“…DRBD3, a protein containing two RRM domains, plays a role both in splicing and mRNA stability in T. brucei (Estévez 2008;Das et al 2012). Also, DRBD13 has been demonstrated to negatively regulate mRNAs encoding for cell membrane-associated proteins via interaction with AREs of the target transcripts (Jha et al 2015). More recently, we showed that the Leishmania infantum Alba3 protein can stabilize the developmentally regulated amastin transcripts specifically in the amastigote stage upon binding to a U-rich element in the 3 ′ UTR (Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 96%